2019
DOI: 10.1172/jci130340
|View full text |Cite
|
Sign up to set email alerts
|

Extrahypothalamic GABAergic nociceptin–expressing neurons regulate AgRP neuron activity to control feeding behavior

Abstract: Arcuate nucleus agouti–related peptide (AgRP) neurons play a central role in feeding and are under complex regulation by both homeostatic hormonal and nutrient signals and hypothalamic neuronal pathways. Feeding may also be influenced by environmental cues, sensory inputs, and other behaviors, implying the involvement of higher brain regions. However, whether such pathways modulate feeding through direct synaptic control of AgRP neuron activity is unknown. Here, we show that nociceptin-expressing neurons in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…In agreement with published data, our study revealed in the tuberal hypothalamus, a strong innervation of MCH and ORX neurons of the LHA and POMC and AgRP neurons of the ARH, all well‐known effectors in the control of appetitive, aversive and goal‐oriented behaviors (Diniz & Bittencourt, 2017; Giardino et al, 2018; González et al, 2016; Jennings et al, 2013; Smith et al, 2019; Sohn, 2015; Stuber & Wise, 2016). Interestingly, in addition of being directly innervated by neurons of the dorsomedial divisions of the BNST, the aforementioned hypothalamic nuclei are also strongly interconnected suggesting a reinforcement of their role in feeding and motivated behaviors (Figure 18).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with published data, our study revealed in the tuberal hypothalamus, a strong innervation of MCH and ORX neurons of the LHA and POMC and AgRP neurons of the ARH, all well‐known effectors in the control of appetitive, aversive and goal‐oriented behaviors (Diniz & Bittencourt, 2017; Giardino et al, 2018; González et al, 2016; Jennings et al, 2013; Smith et al, 2019; Sohn, 2015; Stuber & Wise, 2016). Interestingly, in addition of being directly innervated by neurons of the dorsomedial divisions of the BNST, the aforementioned hypothalamic nuclei are also strongly interconnected suggesting a reinforcement of their role in feeding and motivated behaviors (Figure 18).…”
Section: Discussionsupporting
confidence: 92%
“…Here, we clarified that mostly dorsomedial divisions of the BNST projected onto POMC and AgRP neurons as well as the adjacent septohypothalamic nucleus. In agreement, one recent study confirmed the specific innervation of AgRP/NPY neurons by nociceptin‐expressing neurons of the dorsal divisions of the BNST (Smith et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…BNST is usually considered as a hub for the integration of stress- and anxiety-related behaviors ( Walker et al, 2003 ; Daniel and Rainnie, 2016 ). Its strong connections to hypothalamic nuclei known to control goal-oriented behaviors ( Dong and Swanson, 2006 ; Boutrel et al, 2010 ; Bi et al, 2012 ; Diniz and Bittencourt, 2017 ; Timper and Brüning, 2017 ; Smith et al, 2019 ; Barbier et al, 2021 ) revealed putative functions of these circuits in the stress-related control of feeding. Whereas we recently described the anatomy of the projections from the dorsomedial part of the anterior BNST to hypothalamic nuclei such as the PVH, DMH, ARH, and LHA ( Barbier et al, 2021 ), there is no evidence on the developmental period in which these circuits develop.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the dorsomedial part of the anterior BNST strongly projects onto the paraventricular (PVH), the dorsomedial (DMH), the arcuate (ARH) nuclei, and the lateral hypothalamic area (LHA). In particular, nociceptin-expressing neurons of the dorsomedial part of the BNST control feeding throughout arcuate AgRP neurons ( Smith et al, 2019 ). In addition, corticotropin-releasing hormone (CRH)- and cholecystokinin (CCK)-expressing neurons of the dorsal part of the anterior BNST regulate aversive and appetitive behaviors via neurons of the LHA, including Orexin-expressing neurons ( Jennings et al, 2013 ; Giardino et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Crf and Cck are non-overlapping GABAergic subpopulations that occupy separate lateral vs. medial subdivisions, co-residing in adjacent compartments throughout the middle of the BNST A/P axis, approximately +0.2 to −0.2 mm from Bregma in the mouse. In addition to Crf and Cck , the neuropeptides dynorphin ( Pdyn ), enkephalin ( Penk ), neurotensin ( Nts ), neuropeptide Y ( Npy ), nociceptin ( Pnoc ), somatostatin ( Sst ), substance P ( Tac1 ), neurokinin B ( Tac2 ), and vasopressin ( Avp ) are also found in neurons throughout the BNST (Malsbury and McKay, 1987 ; Walter et al, 1991 ; Poulin et al, 2009 ; Kudo et al, 2014 ; Crowley et al, 2016 ; Ahrens et al, 2018 ; Giardino et al, 2018 ; Zelikowsky et al, 2018 ; Kovner et al, 2019 ; Rigney et al, 2019 ; Rodriguez-Romaguera et al, 2020 ; Smith et al, 2020 ; Whylings et al, 2020 ; Xiao et al, 2020 ; Figure 1A ). Labeling for the calcium-binding protein calretinin appears selective for the dorsolateral (dl)BNST, whereas dopamine receptor type-1 ( Drd1 ) and protein kinase C delta ( Pkcd ) neurons cluster more specifically within the oval nucleus (ovBNST, a discrete subnucleus within the larger dlBNST subregion; Kim et al, 2013 ; Nguyen et al, 2016 ; Pomrenze et al, 2019a ; Wang et al, 2019 ).…”
Section: Molecularly-defined Bnst Cell Typesmentioning
confidence: 99%